Estimasi populasi dan vegetasi habitat Lutung Jawa (Trachypithecus auratus E. Geoffrey 1812) di Gunung Ungaran, Jawa Tengah - Fitri Nur Indah Sari; Karyadi Baskoro; Mochamad Hadi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Javanese Lutung is an endemic Indonesian primate found in Java and Bali. According to the IUCN, these primates are designated as vulnerable species. The purpose of this study was to determine population data and vegetation data of Javanese Lutung habitat. The study was conducted from July to August 2019 at several Mount Ungaran locations, namely Gonoharjo, Semirang, Kalisidi, Medini, Promasan, Jimbaran and Gedongsongo with the line transect method measuring 1 km and repetition three times in each location. Javanese Lutung individual density calculated based on the equation of the Subcommittee on Conservation of Natural Population ranged from 0.94 to 10.3 Ind / km² with an estimated population ranging from 1 to 26 individuals. Javanese Lutung distributed from the height of 565-1421 masl with a group distribution pattern. Found 10 species of tree vegetation in the area of Mount Ungaran. Which is used as a place to feed and break of Javanese Lutung, namely Buluh, Pukuran, Pine, and Puspa trees.